Configurationally Stable Doubly Bridged Biphenyl Azocines through Copper-Catalyzed Double Carbene Insertions into the Corresponding Azepines - Harthong, Steven; Brun, Elodie; Grass, Stéphane; Besnard, Céline; Bürgi, Thomas; Lacour, Jérôme (Synthesis, 2016)
Doubly bridged biphenyl azocines can be prepared in a single step through copper-catalyzed reactions of a doubly bridged biphenyl azepine and diazodiester reagents. Double [1,2]-Stevens rearrangements occur at 100 °C to afford doubly tethered eight-membered rings (49 to 61%) as trans and cis regioisomers (1:1 ratio). These products present an axial chirality. ECD and VCD analyses of the separated enantiomers (CSP-HPLC) were used to assign the absolute configuration. High configurational stability is observed for both regioisomers as racemization does not occur after 1 week of heating at 208 °C in dodecane (ΔG‡ > 41 kcal·mol–1). Interestingly, reactions performed at 40 °C retain a certain level of enantiospecificity (82–86%), avoiding, for the most part, thermal racemization of the starting material.
Keywords: azepine; azocine; carbenes; configurational stability; [1,2]-Stevens rearrangement; ylides